GAS CROMATOGRAPHIC ANALYSIS OF ORGANOPHOSPATE AND PYRETROID COMPOUNDS IN MOSQUITO COILS - Sadli Sadli; Misrahanum Misrahanum (Jurnal Natural, 2011)
Mosquito coils contain active compounds such as chlorpyriphos, dichlorphos, and d-alletrhrin which may be hazardous to the health. As majority of pesticides are stable heat, they can be changed into stable vapor state by column.  a gas chromatographic method of analysis was developed. Gas chromatography for organophosphate compounds, namely chlorpyriphos and dichlorphos, with a OV-17 packed column, and a flame photometry detector equipped by filter for phosphor, which detecs phosphor containing compounds exclusively, avoiding any interference of other non phosphor compounds present in the sample matrix. Gas chromatography for a pyrethoid compound, d-allethrin, utilizes a HP-1 capilarry column with a flame ionization detector, and detect, any ionizable compound. The research was initiated by adjustment of the condition of gas chromatography system to obtain an appropiate separation of compounds a good shape of chromatogram and a tolerable retention time.  With a flow rate of nitrogen 55 ml/min, column temperatures of 210oC, a detector and injector temperature of 230oC, the method gave a retention times chlorpyriphos of 6,47 minute and that of dichlorphos of 0,73 minute . The difference in retention time of chlorpyriphos and that of dichlorphos was caused by the difference in molecular weight of both compounds, thin dichlorphos with a smaller molecular weight (220, 98) was eluted faster than chlorpyriphos (350,6). For  d-allethrin whit a flow rate of nitrogen gas of 40 ml/min, a column temperature  of 180oC, a detector and injector temperature of 210oC, a retention time of d-allethrin of 3,28 minutes was obtained. The mosquito coils tested did not contain any chlorpyriphos nor dichlorphos, and some contained d-allethrin. The d-allethrin content obtained in one of the sample was beyond the tolerated limit.